2005
DOI: 10.1186/1471-2121-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblasts in Hutchinson-Gilford progeria syndrome with the lamin A G608G mutation have dysmorphic nuclei and are hypersensitive to heat stress

Abstract: Background: Hutchinson-Gilford progeria syndrome (HGPS, OMIM 176670) is a rare sporadic disorder with an incidence of approximately 1 per 8 million live births. The phenotypic appearance consists of short stature, sculptured nose, alopecia, prominent scalp veins, small face, loss of subcutaneous fat, faint mid-facial cyanosis, and dystrophic nails. HGPS is caused by mutations in LMNA, the gene that encodes nuclear lamins A and C. The most common mutation in subjects with HGPS is a de novo single-base pair subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…The nuclear abnormalities observed in the p.(Arg331Gln) fibroblasts are in line with the nuclear irregularities observed in fibroblasts of other established pathogenic mutations in LMNA, thereby supporting its pathogenicity. 22,[36][37][38] Like the abnormal nuclear structures in the fibroblasts observed using immunofluorescence, ultrastructural investigation on diseased cells in cardiac tissue with EM also support pathogenicity. The convoluted shapes of the nuclei, blebs, discontinuous layer of heterochromatin, and possible enlarged nuclear pores are features commonly seen in other LMNA mutations.…”
Section: Hoorntje Et Al Mild Phenotype In Lmna P(arg331gln) Carriersmentioning
confidence: 99%
“…The nuclear abnormalities observed in the p.(Arg331Gln) fibroblasts are in line with the nuclear irregularities observed in fibroblasts of other established pathogenic mutations in LMNA, thereby supporting its pathogenicity. 22,[36][37][38] Like the abnormal nuclear structures in the fibroblasts observed using immunofluorescence, ultrastructural investigation on diseased cells in cardiac tissue with EM also support pathogenicity. The convoluted shapes of the nuclei, blebs, discontinuous layer of heterochromatin, and possible enlarged nuclear pores are features commonly seen in other LMNA mutations.…”
Section: Hoorntje Et Al Mild Phenotype In Lmna P(arg331gln) Carriersmentioning
confidence: 99%
“…Primary cultures of dermal fibroblasts were processed for indirect immunofluorescence as described in ref. 17. Rabbit Abs directed against A-type and B-type lamins were kindly provided by N. Chaudhary (Ridgeway Biosystems, Inc., Cleveland) (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained three primary cultures of dermal fibroblasts derived from HGPS patients carrying the LMNA mutation G608G: HGADFN001, HGADFN003, and HGAFN127 from the Progeria Research Foundation (Peabody, MA) and PT001 recently identified in ref. 17. We used in parallel three previously established control dermal fibroblast cultures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations